Penerapan Metode Bermain Peran dalam Meningkatkan Kemampuan Berbicara Anak di RA Ar Raihan - Dewi, Resti Sulistia; Susanti, Reni; Rosmina, Rosmina (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
Speaking ability is an essential skill in early childhood language development. However, many children still struggle to speak fluently and confidently. This study aims to improve children's speaking skills through the implementation of the role-playing method at RA Ar Raihan. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, consisting of two cycles with four stages: planning, implementation, observation, and reflection. The subjects of this study were children at RA Ar Raihan who had difficulties in active speaking. Data were collected through observation, interviews, performance tests, and documentation, then analyzed qualitatively and quantitatively. The results showed that the role-playing method significantly enhanced children's speaking abilities. They became more confident in speaking, had a broader vocabulary, and were able to express their ideas more clearly. Thus, the role-playing method can be an effective strategy in early childhood education to enhance children's speaking skills.